If f(x) = 3x^2 - 4 and g(x) = x+2, find (f - g)(x).
2 answers:
Answer:
3x^2-x-6
Step-by-step explanation:
f(x) = 3x^2 - 4
g(x) = x+2
(f - g)(x)= 3x^2 - 4-( x+2)
Distribute the minus sign
(f - g)(x)= 3x^2 - 4- x-2
Combine like terms
= 3x^2-x-6
Answer:
(f - g)(x) = 3 x² - x - 6
Step-by-step explanation:
<u>Given</u> :-
<u>Find :-</u>
<u>Solution :-</u>
(f - g)(x) = 3 x² - 4 - ( x + 2 )
Distribute the ( - ) minus sign
(f - g)(x) = 3 x ² - 4 - x - 2
Combine like terms
(f - g)(x) = 3 x ² - x - 4 - 2
(f - g)(x) = 3 x² - x - 6
You might be interested in
Idk what linear combination is but you can solve this way:
3x+y=4
-2x-y=-5
x=-1
3(-1)+y=4
-3+y=4
y=7
So x=-1 and y=7
Answer:
f(30)= 75
Step-by-step explanation:
3(30)-15
90-15
75
Answer:
he sum of four consecutive integers is -42.
Step-by-step explanation:
Answer:
2,025
Step-by-step explanation:
Given:
Third term ar² = 45
Seventh term ar⁶ = 3,645
Find:
ar x ar³
Computation:
From 7th term / 3rd term
ar⁶ / ar² = 3,645 / 45
r⁴ = 81
r = 3
So,
ar² = 45
a(3)² = 45
a = 5
So,
ar x ar³
(5)(3) x (5)(3)³
2,025